2021
DOI: 10.1371/journal.pone.0259580
|View full text |Cite
|
Sign up to set email alerts
|

Home, sweet home? The impact of working from home on the division of unpaid work during the COVID-19 lockdown

Abstract: A lockdown implies a shift from the public to the private sphere, and from market to non-market production, thereby increasing the volume of unpaid work. Already before the pandemic, unpaid work was disproportionately borne by women. This paper studies the effect of working from home for pay (WFH), due to a lockdown, on the change in the division of housework and childcare within couple households. While previous studies on the effect of WFH on the reconciliation of work and family life and the division of lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…In this unequal context, the COVID-19 pandemic outbreak has left women worse off and increased the amount of unpaid work-such as child and eldercare-they are expected to do [9,10]. While fathers report increased household chores during the pandemic, mothers increased their childcare and homeschooling responsibilities [11]. One study found that working mothers in the U.K. were 5 percentage points more likely to reduce working hours and 7% more likely to adjust their work patterns than working fathers [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this unequal context, the COVID-19 pandemic outbreak has left women worse off and increased the amount of unpaid work-such as child and eldercare-they are expected to do [9,10]. While fathers report increased household chores during the pandemic, mothers increased their childcare and homeschooling responsibilities [11]. One study found that working mothers in the U.K. were 5 percentage points more likely to reduce working hours and 7% more likely to adjust their work patterns than working fathers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this means that the division of domestic labor remains at least as unequal as it was prior to the pandemic. This striking degree of stability in the aggregate does not mean that there may not have been more pronounced changes for certain subgroups of couples: The increased contributions of male partners seem to be driven mainly by constellations with mothers with a strong labor market attachment without the option to work from home [ 33 , 36 ]. Another German study detected some shift toward the extreme end of the distribution where mothers take over childcare and housework almost completely [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ATUS is of exceptional quality and should prove a useful comparative resource for studying the effects of the pandemic on daily behaviour in the USA. Other time use diary data collection efforts of note during the pandemic outside the UK have taken place in Austria [12], Turkey [13], and a small non-representative (online self-selected) sample in Belgium [14].…”
Section: Review Of Time Use Data and Literaturementioning
confidence: 99%